The Calcutta municipal gazette Tagore memorial special supplement. (Kolkata Kolkata Municipal Corporation and New Age Publishers Pvt., Ltd., 2002)
Festschrift reprinted on the occasion of Rabindranath Tagore's, 1861-1941 one hundred and twenty-fifth birth anniversary; contributed articles on his life and works published as part of the Calcutta Municipal Gazette.
Originally published: Calcutta, 1941.
Includes passages in Bengali.
Keywords: Tagore, Rabindranath -- 1861-1941 -- Criticism and interpretation